Proton density polarization of the doubly magic 40Ca core in 48Ca and EoS parameters. (25th January 2021) - Zenihiro, Juzo; Uesaka, Tomohiro; Sagawa, Hiroyuki; Yoshida, Satoshi
Abstract: The proton density polarization in ${\rm ^{48}Ca}$ by the eight neutrons added on the ${\rm ^{40}Ca}$ core is discussed. We adopt the proton density distributions determined by electron scattering and the neutron density distributions determined by proton elastic scattering in ${\rm ^{40}Ca}$ and ${\rm ^{48}Ca}$ . As a measure of the proton density polarization effect due to the neutrons, a ratio $R$ of the peak values of the neutron density difference $Δρ_{n, {\rm peak}}$ between ${\rm ^{48}Ca}$ and ${\rm ^{40}Ca}$ to the proton one $Δρ_{p, {\rm peak}}$ is introduced and compared with the Hartree–Fock and Hartree calculations by non-relativistic and relativistic energy density functionals (EDFs), respectively. The value $R$ shows clear correlations with the symmetry energy parameters $J$ and $L$, but not with the isoscalar incompressibility $K_∞$ . The experimental value $R$ can be reproduced by theoretical calculations using the EDFs with $L=25$ –50 MeV.